Design, synthesis, biological evaluation, and molecular modeling studies of rhodanine derivatives as pancreatic lipase inhibitors. Issue 10 (13th August 2019) - Chauhan, Divya; George, Ginson; Sridhar, S. N. C.; Bhatia, Rohit; Paul, Atish T.; Monga, Vikramdeep
Abstract: A series of rhodanine‐3‐acetic acid derivatives were synthesized via Knoevenagel condensation of rhodanine‐3‐acetic acid with various substituted aromatic aldehydes. The synthesized derivatives were screened in vitro for understanding the inhibitory potential towards pancreatic lipase (PL), a key enzyme responsible for the digestion of dietary fats. Derivative8f exhibited a potential inhibitory activity towards PL (IC50 = 5.16 µM), comparable to that of the standard drug, orlistat (0.99 µM). An increase in the density of the aromatic ring resulted in potential PL inhibition. The enzyme kinetics of8f exhibited a reversible competitive‐type inhibition, similar to that of orlistat. Derivative8f exhibited a MolDock score of ‐125.19 kcal/mol in docking studies, and the results were in accordance with their PL inhibitory potential. Furthermore, the reactive carbonyl group of8f existed at a distance adjacent to Ser152 (≈3 Å) similar to that of orlistat. Molecular dynamics simulation (10 ns) of the8f ‐PL complex revealed a stable binding conformation of8f in the active site of PL (maximum root mean square displacement of ≈2.25 Å). The present study identified novel rhodanine‐3‐acetic acid derivatives with promising PL inhibitory potential, and further lead optimization might result in potent PL inhibitors. Abstract : A series of new rhodanine acetic acid derivatives were synthesized and structurally characterized. Pancreatic lipase inhibition assays were performed for various synthesized derivatives (8a‐n ) by using (PNPB) p‐nitrophenyl butyrate as substrate. Compound8f exhibited the most potent and reversible competitive inhibition (IC50 = 5.16 μM). The molecular dynamics of8f indicated its stable binding conformation (root mean square displacement ≈2.5 Å).